2008
DOI: 10.1111/j.1440-1827.2008.02236.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of myelodysplastic syndrome and aplastic anemia by immunostaining of p53 and hemoglobin F and karyotype analysis: Differential diagnosis between refractory anemia and aplastic anemia

Abstract: P53 mutation has been reported in various solid tumors, acute leukemia and myelodysplastic syndrome (MDS), but the diagnostic significance of p53 in MDS remains to be determined. The purpose of the present paper was to examine p53 mutation and immunostaining of the same patients, because there have been few reports of simultaneous analysis of these markers. Seven p53 mutations were observed among 37 MDS and 11 cases of overt leukemia transformed from MDS (MDS-OL). Mutated p53 mainly observed in high-risk MDS h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…The monoclonal antibody, DO-1 (Santa Cruz, Biotechnology, Inc.), which recognizes both wild-type and mutant p53 proteins, was used as the primary antibody to detect p53 protein expression (Ventana, BenchMark XT iVIEW DAB v3). The staining of the p53 signals was evaluated at high magnification (100x objective) in randomly selected fields and scored as negative, weak (p53 + /light brown), or strong (p53 ++ /dark brown) nuclear staining according to Iwasaki et al 23 At least 300 cells were counted. Immunohistochemical studies for p53 were also performed on 20 normal bone marrow samples (control group).…”
mentioning
confidence: 99%
“…The monoclonal antibody, DO-1 (Santa Cruz, Biotechnology, Inc.), which recognizes both wild-type and mutant p53 proteins, was used as the primary antibody to detect p53 protein expression (Ventana, BenchMark XT iVIEW DAB v3). The staining of the p53 signals was evaluated at high magnification (100x objective) in randomly selected fields and scored as negative, weak (p53 + /light brown), or strong (p53 ++ /dark brown) nuclear staining according to Iwasaki et al 23 At least 300 cells were counted. Immunohistochemical studies for p53 were also performed on 20 normal bone marrow samples (control group).…”
mentioning
confidence: 99%
“…18,[23][24][25][29][30][31][32][33][34] TP53 mutations occur primarily in high-risk/therapy-related MDS, MDS-derived leukemia, and in the context of complex chromosomal abnormalities including del(17p). 11,12,14,15,[18][19][20]35,36 Studies also reported on the poor prognostic impact of TP53 mutations and the association between TP53 mutations and poor therapy response.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] In order to minimize the possibility of false positive results, p53 protein expression was considered positive only if strong nuclear staining (score 3+) was present in at least 5% of hematopoietic cells in the entire BM. 6,9 To ensure correct staining, a positive control (urothelial carcinoma) was included on each slide. Molecular TP53 mutation analysis was performed by deep sequencing, as described previously.…”
mentioning
confidence: 99%